Analisis Pengaruh Faktor Eksternal: Tingkat Inflasi, Suku Bunga BI, dan Pertumbuhan Ekonomi (GDP) terhadap Risiko Kredit Pada Bank Syariah (NPF) - sucik lestari; Khoiriyah, Rahmawati (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2024)
This research aims to analyze the influence of inflation, BI interest rates, and economic growth (GDP) on NPF (Non-performing Financing). This study was conducted on Sharia Banks registered with Sharia Commercial Banks (BUS) in 2018-2022. The data used is secondary data from the annual reports of Sharia Banks. The sampling technique was purposive sampling, obtaining a research sample of 55 data. The research method used is a quantitative research method using data analysis techniques, namely panel data regression analysis, while data processing uses the Eviews 10 program. The research results show that the BI interest rate has a positive effect on NPF (Non-performing financing). Meanwhile, inflation and economic growth (GDP) has a negative effect on NPF (Non-performing financing).